2008
DOI: 10.1111/j.1600-051x.2008.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual pockets on progression of periodontitis and tooth loss: Results after 11 years of maintenance

Abstract: Residual PPD>or=6 mm represent an incomplete periodontal treatment outcome and require further therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
607
8
29

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(700 citation statements)
references
References 28 publications
56
607
8
29
Order By: Relevance
“…As suggested, the magnitude of changes during SPT appears related to the initial defect size at site level and to heavy smoking at patient level (Matuliene et al. 2008). Moreover, a local effect of smoking appears to be superimposed on the systemic effect, particularly affecting maxillary single‐rooted teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested, the magnitude of changes during SPT appears related to the initial defect size at site level and to heavy smoking at patient level (Matuliene et al. 2008). Moreover, a local effect of smoking appears to be superimposed on the systemic effect, particularly affecting maxillary single‐rooted teeth.…”
Section: Discussionmentioning
confidence: 99%
“…1996a, Matuliene et al. 2008). In contrast, long‐term follow‐up studies have not found an association between smoking status and tooth loss (Fisher et al.…”
mentioning
confidence: 99%
“…The present study also showed a continuous decrease in the plaque index with professional toothbrushing combined with chlorhexidine prior to scaling. In other words, meticulous removal of supragingival plaque, including bacteria accumulated around the gingival margin, was especially important in controlling and preventing periodontal disease A study by Matuliene et al 35 reported a full-mouth bleeding score of 30 or more to be a risk factor for tooth loss. The mean BoP score in the early intervention group was 32.4% in the present study, indicating unhealthy gingiva.…”
mentioning
confidence: 99%
“…After careful consideration, the final prosthesis was placed to obtain recovery of oral function. An association has been demonstrated between deep periodontal pockets resulting from alveolar bone destruction and an increase in the number of tooth lost 12) . Although extraction was indicated for tooth #17, it was preserved during periodontal surgery.…”
Section: Discussionmentioning
confidence: 99%